TINJAUAN EKONOMI SYARIAH TERHADAP SISTEM JUAL BELI KOPI SECARA TENDER (STUDI KASUS KECAMATAN LATIMOJONG KABUPATEN LUWU) - Muhammad Ruslan Abdullah; Rasmawati Ilham Patintingan (Al-Amwal : Journal of Islamic Economic Law, 2017)
The purpose of this study was to find out (1) the form of implementation of coffee buying and selling in tenders in Latimojong District, Luwu Regency, (2) Islamic economic views on the coffee buying and selling system in tenders in Latomojong, Luwu Regency. This research is a qualitative study using the type of social research and syar'i. Using data collection methods from literature studies (literature studies) and field research (field studies) with interview techniques directly to sellers and buyers in Latimojong District by giving specific questions about research. The results of the study revealed how to sell coffee with tenders in Latimojong Subdistrict, where sellers install prices will first use the seller using a bargaining system, after the buyer sees the Coffee location then buys a bargain at the price provided by the previous seller then bargains with willingness. Based on the Islamic economic view of the coffee buying and selling system in Latimojong Subdistrict if it is reviewed from the implementation of buying and selling based on harmony and the terms of buying and selling in accordance with Islamic Sharia regulations, because of Islamic pillars and buying conditions to buy coffee in Latimojong Subdistrict, Luwu Regency there are sellers, buyers, ijab and qabul and there are items that are traded. Not included in gharar because the quality, price, price, and time of delivery are clear.